Consequences of regulatory fit for leader–follower relationship quality and commitment. Issue 3 (18th May 2017) - Johnson, Russell E.; Lin, Szu‐Han (Joanna); Kark, Ronit; Van Dijk, Dina; King, Danielle D.; Esformes, Einat
Abstract : A central tenet of regulatory focus theory is that people hold more positive appraisals and exhibit greater dedication when their regulatory focus is congruent with the orientation of the immediate context, a phenomenon known as regulatory fit. Unfortunately, scant attention has been paid to regulatory fit in interpersonal contexts and the consequences of relationship partners having congruent promotion and prevention foci. Integrating regulatory fit theory with theories of relational leadership, we predicted that regulatory fit would enhance relationship quality and commitment within leader–follower dyads. These predictions were examined across three samples, using data collected from multiple sources and at multiple times. Our results indicated that promotion fit, prevention fit and the interaction between them predicted relationship quality and commitment to the leader, which in turn predicted leader‐targeted citizenship behaviour and withdrawal cognition. These relationships remained after controlling for demographic fit and followers' and leader's individual regulatory foci. Practitioner points: Leader–follower regulatory fit predicts high‐quality relationship with one's supervisor. Leader–follower promotion fit predicts affective commitment to supervisor. Leader–follower prevention fit predicts normative commitment to supervisor. Promotion fit and prevention fit interact to have synergistic effects on outcomes.